Purification, characterization, and localization of a protein antigen shared by thermophilic campylobacters. - Dubreuil, J D (1990)
A protein antigen with an apparent molecular weight (Mr) of 31,000 was isolated from 0.2 M glycine hydrochloride (pH 2.2) extracts of a typical human fecal isolate, Campylobacter jejuni VC74. The protein was purified to homogeneity on a preparative scale by immunoaffinity chromatography followed by molecular sieving with a Superose 12 column. Isoelectric focusing under nondenaturing conditions indicated a pI of 9.3, and amino acid composition analysis showed that the protein was unusually rich in lysine, containing 14.9 mol% of this basic amino acid. Cysteine and tryptophan were absent. The protein also contained approximately 35% hydrophobic amino acid residues, and N-terminal amino acid analysis showed that 17 of the first 38 residues were hydrophobic. This amino-terminal sequence to residue 22 was virtually identical to that of an antigenically cross-reactive 31,000-Mr protein isolated from another C. jejuni strain belonging to a different heat-labile serogroup. Western blotting (immunoblotting) of glycine extracts of other C. jejuni, Campylobacter coli, and Campylobacter laridis strains belonging to different thermolabile and thermostable serotypes, as well as Campylobacter fetus, with a rabbit polyclonal antiserum raised against the purified C. jejuni VC74 protein showed that all C. jejuni, C. coli, and C. laridis strains tested contained a 31,000-Mr protein with epitopes which were antigenically cross-reactive with the C. jejuni VC74 protein. The antigenically cross-reactive epitopes of this protein were also readily detected by immunodot blot assay of glycine extracts of C. jejuni, C. coli, and C. laridis with monospecific polyclonal antisera to the 31,000-Mr protein, suggesting that this serological test could be a useful addition to those currently employed in the rapid identification of these important pathogens. Slide agglutination reactions, immunofluorescence assay, and immunogold electron microscopy with antisera to purified 31,000-Mr protein and trypsin treatment of whole cells indicated that the cross-reactive epitopes of the 31,000-Mr protein were not exposed on the cell surface. Cell fractionation analysis and immunogold electron microscopy located the protein on the outer surface of the cytoplasmic membrane. This finding suggests that the 31,000-Mr protein is not a good candidate for inclusion in a monovalent subunit Campylobacter vaccine.